2015
DOI: 10.1016/j.cofs.2015.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Physics of food structure breakdown and bolus formation during oral processing of hard and soft solids

Abstract: Please cite this article as: Witt, T., Stokes, J.R.,Physics of food structure breakdown and bolus formation during oral processing of hard and soft solids, COFS (2015), http://dx.doi.org/10. 1016/j.cofs.2015.06.011 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 63 publications
(52 reference statements)
2
44
0
Order By: Relevance
“…Laguna, Asensio Barrowclough, Chen, and Sarkar () studied the eating difficulty of six products (carrot, banana, mozzarella, potato, soft cheddar, and hard cheddar) and found that the hardest food, carrot required a greater number of chews and the longest processing time in mouth, which they found in accordance with the conclusion by Witt and Stokes (). However, hard cheddar was found the most difficult although it resided a shorter time in mouth and the break force was lower than carrot, which led these authors to think that it is not only the force at break but also the structural property of the food that plays an important role in perceived difficulty.…”
Section: Texture Studies Of Solid Foodssupporting
confidence: 61%
“…Laguna, Asensio Barrowclough, Chen, and Sarkar () studied the eating difficulty of six products (carrot, banana, mozzarella, potato, soft cheddar, and hard cheddar) and found that the hardest food, carrot required a greater number of chews and the longest processing time in mouth, which they found in accordance with the conclusion by Witt and Stokes (). However, hard cheddar was found the most difficult although it resided a shorter time in mouth and the break force was lower than carrot, which led these authors to think that it is not only the force at break but also the structural property of the food that plays an important role in perceived difficulty.…”
Section: Texture Studies Of Solid Foodssupporting
confidence: 61%
“…Hayakawa et al (2014) assessed the eating difficulty using a trained panel; they found that the difficulty to eat a food is reflected by the time of consumption. Also, Witt and Stokes (2015) recently reported that harder gels, require more oral residence time at mouth, more chewing and a greater muscle force. Carrot was the hardest food product given, which required more number of chews and resided longer in mouth, being in accordance with Witt and Stokes (2015).…”
Section: Oral Processing and Physical Propertiesmentioning
confidence: 99%
“…Also, Witt and Stokes (2015) recently reported that harder gels, require more oral residence time at mouth, more chewing and a greater muscle force. Carrot was the hardest food product given, which required more number of chews and resided longer in mouth, being in accordance with Witt and Stokes (2015). However, comparing all the food given, hard cheddar was perceived as the most difficult one, although it resided shorter time at mouth and broke at lower force than carrot (former being softer).…”
Section: Oral Processing and Physical Propertiesmentioning
confidence: 99%
“…Oral processing of solid or semisolid food (modified from Foster et al., ; Stokes et al., ; Witt & Stokes, ).…”
Section: Dysphagiamentioning
confidence: 99%
“…The third hardness level (under 2 × 10 4 N/m 2 and viscosity over 1500 mPa·s) refers to foods that can be broken up by tongue. Finally, the fourth hardness level (under 5 × Foster et al, 2011;Stokes et al, 2013;Witt & Stokes, 2015). Table 1-Textural properties of dysphagia diets of various levels (modified from Yoshioka et al, 2016 andPark et al, 2017).…”
Section: Desired Characteristics Of Dysphagia Foodsmentioning
confidence: 99%